ANALISIS PEMBENTUK EFIKASI DIRI PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR MELALUI FAKTOR EKSTERNAL - Hardina Maulida Fashiha; Neni Mariana; Mochamad Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Like a fish in the open sea, not just in an aquarium, which illustrates the researcher openness to the wider world. After the researcher finds an understanding of herself, then the researcher will relate to the outside world. The researcher reflects in depth on the transformation that exists in the researcher and explores how external factors in students can influence self-efficacy in learning elementary school mathematics. This research is a transformative qualitative type that uses the method of writing as inquiry, writing critical auto|ethnography to help researcher understand the experience of being student, student of university, and teacher. Researcher also used postmodern interviews to find out the views of students, teachers, and parents on the formation of students' self-efficacy in learning mathematics. The results of auto|ethnography studies, literature studies, and interviews show that there are external factors in the form of verbal persuasion from parents, teachers, and friends that influence students' self-efficacy in learning mathematics. The verbal persuasion that students receive comes from the people around them, who are the people closest to them; so the researcher chose to call it a closest person verbal persuasion. Through this research, researcher and research subjects can change the view that external factors in the form of verbal persuasion from people closest to them can shape students' self-efficacy in learning mathematics. Therefore, the formation of self-efficacy through external self learners can be well controlled by external parties. Controlling the formation of self-efficacy is intended so that students develop good self-efficacy in learning mathematics. Keywords: external factors, self-efficacy, mathematic learning.